IMPROVING STUDENTS’ SPEAKING SKILL THROUGH READERS THEATRE - Anita Agustin; Machdalena Vianty; Zuraida Zuraida (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2015)
Abstract: The objectives of this study were to find out whether or not: (1) there was any significant improvement in speaking skill of the eleventh grade students of SMA N 14 Palembang after they were taught by using Readers Theatre, (2) there was any significant improvement in each aspect of speaking skill of the eleventh grade students of SMA N 14 Palembang after they were taught by using Readers Theatre, and (3) there was any significant difference in speaking skill between students who were taught by using Readers Theatre and those who were not taught by using Readers Theatre. The sample of this study was 60 eleventh grade students of SMA N 14 Palembang, who were divided into control and expreimental groups, and each group had 30 students. To collect the data, each group was given a pretest and a posttest. The data were analysed using paired sample t test and independent sample t-test. The result showed: (1) there was a significant improvement in students‟ speaking skill of the experimental group after they were taught by using Readers Theatre (mean diff=22.10; p-value=.000), (2) the mean score of each aspect of speaking skill in the posttest was higher than in the pretest and p-values were <0.05 and (3) the mean difference of posttest of experimental group was significantly higher than the control group (p-value=.000). In conclusion, Readers Theatre can be used to improve student‟s speaking skill.Key words: Improving Speaking Skill, Readers Theatre, eleventh graders